AN ANALYSIS OF THE STANDARD DEVIATION OF THE ENTROPY PARAMETER FOR TARGET DETECTION ON THE BACKGROUND CLUTTER - Pham , T.; Nguyen , T.; Nguyen , V. (EurasianUnionScientists, 2021)
The paper proposes a method to improve the performance of target detection on the background clutter using the standard deviation of polarization entropy H parameter. The performance of target detection is analyzed with different types of target, on the background clutter models Rayleigh, Weibull and Laplace. Also examined the special case when the target has the same H parameter as the background clutter. The results showed that the performance of the method using the standard deviation of H in the target detection on the background clutter has increased significantly compared to the case where only the H parameter is used.